Hungarian Monitoring, 10 June 1990 . [Magyar rádiófigyelő], 1990. június 10 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International politics: - Elections in Czechoslovakia - Lithuanian conflict - Bulgarian elections - Mass rally of national movements in Kyrgyzstan Domestic affairs: - Collecting signatures on the method of electing the president - Polish president visits Hungary - Remembering the 1953 prisoners' uprising in Tiszalök Külpolitika: - Választások Csehszlovákiában - A litván konfliktus - Bolgár választások - A nemzeti mozgalmak nagygyűlése Kirgizisztánban Belpolitika: - Aláírásgyűjtés a köztársasági elnök megválasztásának módjáról - A lengyel elnök magyarországi látogatásáról - Emlékezés a tiszalöki 1953-as fogolylázadásra